Formation of intermetallic particles during solidification and homogenisation of two Al–Mg–Si alloys. Issue 1 (2nd January 2023) - Engler, Olaf; Schröter, Torsten; Krause, Christopher
Abstract : Several key properties of aluminium semi-finished products, including formability, softening behaviour, strength and ductility, are influenced by the constitution of alloying elements in solid solution or in precipitated form, i.e. by the materials microchemistry. In the present paper, we study microchemistry reactions in two Al–Mg–Si automotive sheet alloys, AA 6005C and AA 6016, with different Mg:Si ratios. The formation of constituent phases and dispersoids during solidification and subsequent homogenisation is analysed by scanning electron microscopy and measurements of the specific electrical resistivity. Type, composition and volume fraction of the constituent phases in the as-cast state are assessed with the Alstruc solidification model. The changes in solute level and precipitation during homogenisation are traced with a statistical microchemistry simulation tool termed ClaNG.